Issue Notes - , Editor (Historical Papers, 2022)
The following papers were presented to the Canadian Society of Church History, but were not made available for publication: Lucille Marr, “Anne Synder, the Mennonite Central Committee, and Post-construction Germany”; Marvin L. Anderson, “Crossing Borders, Crossing Boundaries: The ‘Free Trade’ in Religious Ideas in the Theoretical Formation of Prairie Populism”; Mary-Ann Shantz Lingwood, “The Family that Prays Together Stays Together: Calgary’s Anglican Churches and the Christian Family Ideal, 1950-1970”; Andrew Mark Eason, “Revivalism, Religious Liberty, and the Colonial State: The Salvation Army in Late-Victorian Bombay, 1882-1883”; Michael Power, “From Frontier Priest to Urban Pastor: Father Edmund Burke Kilroy”; Marilyn Färdig Whiteley, “The Silence of Isabel Crawford, Missionary to the Kiowa”; and Sandra Beardsall, “Who Killed Ray Hord? Prophecy and Death in the Secular City.”